Strategic management and competitive advantage : concept and cases. - Barney, Jay B., 1954-; Hesterly, William S., ....- (Upper Saddle River : Pearson, 2006)
PART ONE- The Tools of Strategic Analysis Chapter 1 What Is Strategy and the Strategic Management Process? Chapter 2 Evaluating a Firm's External Environment Chapter 3 Evaluating a Firm's Internal Capabilities Cases- Roadway Express; Apple iTunes; Michelin and the Global Tire Industry; Wal-Mart Stores, Inc.; Harlequin Enterprises PART TWO- Business Level Strategies Chapter 4 Cost Leadership Chapter 5 Product Differentiation Cases- British Motorcycle Industry; JetBlue; Kodak; Levi's; Nike, Inc. PART THREE- Corporate Strategies Chapter 6 Vertical Integration Chapter 7 Corporate Diversification Chapter 8 Organizing to Implement Corporate Diversification Chapter 9 Strategic Alliances Chapter 10 Mergers and Acquisitions Cases- Nucleon, Inc.; LVMH; Ben & Jerry's- Japan;Ebay; The Tale of Eloise and Abelard; Extending the Easy Business Model; Lego; SwissAir; Newell Company; Saatchi & Saatchi; Cooper Industries
Keywords: Bedrijfsorganisatie